Representing Youth of India by Chetan Bhagat in His Works - Kaur, Japneet; Kaur, Komalpreet (International Journal of Psychosocial Rehabilitation, 2020)
The current youth is extremely fiery, imaginative, innovative, vivacious and ready to effectively achieve their optimal goal. However, close by this huge number of They have positive attributes such as being crazy, temperamental, impolite, and childlike. They are not forthcoming about their positions and commitments. They are powerful when they neglect getting what they want. The creation of this 'New India' brand goes with the undertaking to fabricate another age Indian subject who will expect a fundamental part in depicting this new changed country. Bhagat's books and legends are, somewhat, representative of the new age Indian youth in more ways, as his books local area on the components of metropolitan life and the effect of monetary movement among this new age Indian youth. In the 21st century, any place in the world, youth is considered as the power of its country. In addition it's genuine as the country can turn out to be strong given that its puberty is contributing for the progress of the country. At any rate the countries are attempting to do a ton for youth yet obviously they are stressed over them as they are now and again consuming their time for worthless things or including limit with respect to wrong works, and so on.